COMPARATIVE STUDY OF SOFTWARE PREFERENCES AND BUILDING TYPOLOGY IN ARCHITECTURAL DESIGN STUDIO - Dharmatanna, Stephanus Wirawan; Wijaya, Elvina Shanggrama (Border: Jurnal Arsitektur, 2024)
The developments of information technology have affected architectural education methods significantly, especially in the usage of architectural design softwares throughout the design process. Proficiency to operate certain software has become one of important considerations in professional architectural practice, because such skill will affect the whole process and outputs. With excellent skill, one can visualize and communicate design more effectively, rather than other individuals that use more updated software features but still learning to operate them. On the other hand, the learning process in architectural design studios always has a theme that can be classified to certain building typologies. This research aims to study the relation between building typology and software preferences in each design stage, from students point of view. The targeted students are the ones in third and fourth year of study, where the digital media are utilized in the studio process. The data obtained from questionnaires will be analyzed further using descriptive and correlational analysis. The findings from this research will serve as an input for the development of architectural education curriculum, regarding the most relevant and beneficial architectural software in each design process, from students' preferences.